2005
DOI: 10.1073/pnas.0502240102
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila host defense after oral infection by an entomopathogenic Pseudomonas species

Abstract: Drosophila has been shown to be a valuable model for the investigation of host-pathogen interactions. Study of the Drosophila immune response has been hampered, however, by the lack of true Drosophila pathogens. In nearly all studies reported, the bacteria used were directly injected within the body cavity of the insect, bypassing the initial steps of a natural interaction. Here, we report the identification of a previously uncharacterized bacterial species, Pseudomonas entomophila (Pe), which has the capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
485
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 408 publications
(513 citation statements)
references
References 26 publications
15
485
0
1
Order By: Relevance
“…when the Erwinia persistence factor evf is overexpressed in Erwinia strains, infected larvae stop feeding (suggesting a food-uptake blockage), bacteria proliferate and a strong lethality is observed 36,37 . A third example of toxicity towards the insect gut is observed with P. entomophila, a bacterium that can infect and kill D. melanogaster larvae and adults after ingestion 31 . D. melanogaster infection by P. entomophila is also characterized by a cessation of feeding.…”
Section: Pathogenicmentioning
confidence: 99%
See 4 more Smart Citations
“…when the Erwinia persistence factor evf is overexpressed in Erwinia strains, infected larvae stop feeding (suggesting a food-uptake blockage), bacteria proliferate and a strong lethality is observed 36,37 . A third example of toxicity towards the insect gut is observed with P. entomophila, a bacterium that can infect and kill D. melanogaster larvae and adults after ingestion 31 . D. melanogaster infection by P. entomophila is also characterized by a cessation of feeding.…”
Section: Pathogenicmentioning
confidence: 99%
“…D. melanogaster infection by P. entomophila is also characterized by a cessation of feeding. Electron microscopy observations showed that infection with P. entomophila causes a loss of larval midgut integrity 31 . Comparative transcriptome analysis of D. melanogaster larvae orally infected by P. entomophila or E. c. carotovora 15 revealed that the expression of 205 genes is altered during a lethal infection compared with a non-lethal infection.…”
Section: Pathogenicmentioning
confidence: 99%
See 3 more Smart Citations